2008
DOI: 10.1086/590434
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal Influenza Vaccine Administered Using a New Microinjection System Produces Superior Immunogenicity in Elderly Adults: A Randomized Controlled Trial

Abstract: Clinicaltrials.gov registry number: NCT00296829.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
180
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 241 publications
(191 citation statements)
references
References 31 publications
6
180
0
4
Order By: Relevance
“…Table 2 reports HI antibody responses induced following administration of ID vaccine using BD's Soluvia to volunteers aged 60 y in the 9 different clinical studies considered in the present review. [28][29][30][31]41,[57][58][59][60] In the study by Arnou et al 28 the results over 3 consecutive years were reported and in one study 58 ) only the results for A/H3N2 strain were included. The total number of subjects examined was 5035 for A/H3N2 and 5100 for A/H1N1 and B antigens.…”
Section: Immunogenicity Of Fluad and Intanza 15mcg ò In Elderly Peoplmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 reports HI antibody responses induced following administration of ID vaccine using BD's Soluvia to volunteers aged 60 y in the 9 different clinical studies considered in the present review. [28][29][30][31]41,[57][58][59][60] In the study by Arnou et al 28 the results over 3 consecutive years were reported and in one study 58 ) only the results for A/H3N2 strain were included. The total number of subjects examined was 5035 for A/H3N2 and 5100 for A/H1N1 and B antigens.…”
Section: Immunogenicity Of Fluad and Intanza 15mcg ò In Elderly Peoplmentioning
confidence: 99%
“…Although a number of results were available, 2 meta-analysis on IM-MF59 26,27 and 2 randomized controlled trials on ID 28,29 including safety data in adults >60 y of age with and without underlying diseases were identified. These studies included trials comparing IM-MF59 or ID with non-adjuvanted influenza vaccines; however we considered results concerning the 2 potentiated vaccines only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trial results obtained to date reveal no safety issues with either the 9‐ or the 15‐μg formulation of the intradermal vaccine 29 , 40 . The rates of solicited systemic reactions and unsolicited adverse events observed in each trial performed to date have been comparable between intradermal and intramuscular groups.…”
Section: Intradermal Vaccine Against Seasonal Influenzamentioning
confidence: 99%
“…In a phase 2 study, the immunogenicity and safety of two different intradermal vaccine formulations containing 15 or 21 μg of haemagglutinin per strain were compared with that of Vaxigrip ® , which contains 15 μg of haemagglutinin per strain 29 . The study was designed to test whether one or both of the investigational intradermal vaccines induced statistically superior immune responses compared with the control vaccine.…”
Section: Intradermal Vaccine Against Seasonal Influenzamentioning
confidence: 99%